Analysis of incidents notified in a general hospital - Mirela Lopes de Figueiredo; Carla Silvana de Oliveira e Silva; Maria Fernanda Santos Figueiredo Brito; Maria D'Innocenzo
ABSTRACT Objective: To evaluate the incidents spontaneously notified in a general hospital in Minas Gerais. Method: Retrospective, descriptive, quantitative study performed at a general hospital in Montes Claros - Minas Gerais State. The sample comprised 1,316 incidents reported from 2011 to 2014. The data were submitted to descriptive statistical analysis using Statistical Package for the Social Sciences version 18.0. Results: The prevalence of incidents was 33.8 per 1,000 hospitalizations, with an increase during the investigation period and higher frequency in hospitalization units, emergency room and surgical center. These occurred mostly with adult clients and relative to the medication supply chain. The main causes were noncompliance with routines/protocols, necessitating changes in routines and training. Conclusion: There was a considerable prevalence of incidents and increase in notifications during the period investigated, which requires the attention of managers and hospital staff. Nevertheless, we observed development of the patient safety culture.